CONSUMER TRUST AND LOYALTY ON TRANSPORTATION SERVICE BUSINESS - David Luhur Pambudi; Sri Rahayu; Susi Sulastri; Wulandari Wulandari (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study aims to determine the marketing strategy implemented by the Dalupa Trans Lampung East bus rental service company, to increase consumer loyalty through consumer trust and satisfaction. This research method uses a quantitative approach. The population in this study were consumers, tenants and passengers of the Dalupa Trans Bus, totaling 333. The sampling technique uses the Purposive Sampling Technique, with the criteria of respondents being consumers who have rented a Dalupa Trans Bus, at least 2 times, at least 17 years old, male or female. Data collection techniques through distributing questionnaires to respondents who meet the criteria. The data analysis method used is Multiple Linear Analysis with the SPSS ( Stistics Product and Service Solution) program . The results of the study prove that consumer trust has a significant effect on consumer loyalty. Consumer satisfaction does not have a significant effect on consumer loyalty. But simultaneously consumer trust and customer satisfaction have a positive and significant effect on consumer loyalty. The conclusions from this study prove that the higher consumer trust, the higher consumer loyalty will also increase, while consumer satisfaction is not able to increase consumer loyalty. Keywords: Consumer Trust, Consumer Satisfaction, Consumer Loyalty, Marketing, Service Business.